Torsion of Fatty Appendage of Falciform Ligament: Acute Abdomen in a Child. (18th November 2015) - Maccallum, Caroline; Eaton, Sarah; Chubb, Daniel; Franzi, Stephen
Abstract : Torsion of the fatty appendage of the falciform ligament is an extremely rare condition that leads to severe abdominal pain and raised inflammatory markers. It can be recognised on ultrasound or CT scan. The pathophysiology is the same as that involved in the more common torsion and/or infarction of the greater omentum or epiploic appendages. The condition is best managed conservatively with anti-inflammatory analgesia, and the early recognition of this type of torsion may prevent unnecessary operative intervention to look for a source of abdominal pain. There have been five reported adult cases of a torted fatty appendage of the falciform ligament identified on ultrasound and CT scan, but no paediatric cases. We report a case of torsion of the fatty appendage of the falciform ligament in a ten-year-old boy and describe its imaging characteristics on CT scan.